2015
DOI: 10.1371/journal.pone.0115838
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dyspepsia on Symptom Severity and Quality of Life in Adults with Headache

Abstract: BackgroundDyspepsia and headache frequently co-exist, but the clinical implication of this association is uncertain. We planned to examine the prevalence and impact of dyspepsia in adults with headache.MethodsA cross-sectional study was conducted in a secondary care setting. Clinical, psychological and health-related quality of life (HRQOL) data were compared between subjects with headache and controls (non-headache subjects). The impact of dyspepsia was analysed further in subjects with headache alone.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
(35 reference statements)
0
4
0
2
Order By: Relevance
“…Abnormal visceral mechanosensory and vagal function has been found to be involved in dyspeptic patients, and disturbances in visceral nerves have also been implicated in migraines ( 7 , 24 ). In addition, individuals with headaches and GI symptoms had more severe and frequent symptoms compared to those subjects without GI symptoms ( 8 , 25 , 26 ). A possible explanation for this effect may be a heightened common pathophysiological mechanism, which may lead to more severe symptoms in individuals with dual pathology compared to just headaches alone ( 25 ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Abnormal visceral mechanosensory and vagal function has been found to be involved in dyspeptic patients, and disturbances in visceral nerves have also been implicated in migraines ( 7 , 24 ). In addition, individuals with headaches and GI symptoms had more severe and frequent symptoms compared to those subjects without GI symptoms ( 8 , 25 , 26 ). A possible explanation for this effect may be a heightened common pathophysiological mechanism, which may lead to more severe symptoms in individuals with dual pathology compared to just headaches alone ( 25 ).…”
Section: Discussionmentioning
confidence: 90%
“…In addition, individuals with headaches and GI symptoms had more severe and frequent symptoms compared to those subjects without GI symptoms ( 8 , 25 , 26 ). A possible explanation for this effect may be a heightened common pathophysiological mechanism, which may lead to more severe symptoms in individuals with dual pathology compared to just headaches alone ( 25 ).…”
Section: Discussionmentioning
confidence: 90%
“…A previous study using EQ-5D in a secondary care hospital setting, patients with dyspepsia and headache had greater severity of the latter symptom resulting in lower scores for HRQOL compared to those without dyspepsia. [11]…”
Section: Discussionmentioning
confidence: 99%
“…Sullivan et al have reported that pediatric patients with chronic upper GI symptoms may have underlying OD, and that for patients with upper GI symptoms and OD, treatment of OD might help to resolve GI symptoms . With regard to headache, recent studies have shown that dyspepsia is strongly associated with headache …”
Section: Discussionmentioning
confidence: 99%